Model for allocating the share of the land component from the assessment of the market value of single real estate objects - V. D. Kreshchensky; D. M. Sharieva; M. B. Laskin (Статистика и экономика)
The objective of the study is to develop a mathematical model and corresponding methodology that allows, based on available empirical observations (market data), in a comparative approach, to create an assessment of the market value of a single real estate object and to allocate in its composition the share of the value attributable to the land plot. Such tasks arise due to the need for separate accounting of taxable objects: land and real estate located on it. The relevance of the study is determined by the introduction of the institute of cadastral valuation in the Russian Federation. The legislation provides for the frequency of cadastral valuation every four years, in cities of federal significance, the term of the next valuation can be set at two years, by decision of the subject of the federation. It should be noted that when determining the cadastral value by mass appraisal methods, the methodological recommendations of Rosreestr essentially speak of determining the cadastral value as a market value.Materials and methods. A model of a multivariate logarithmic normal distribution law is considered. Such a model is a theoretical prerequisite for developing multiplicative models (i.e. additive for the logarithms of prices and some price-forming factors). The data from open Russian Internet resources on sales of single real estate objects (houses) and vacant land plots in the Leningrad region, put up for sale in 2023, are used. The sample sizes for houses are 2759 records, for vacant land plots - 1023 records. The authors propose a method for estimating the share of the land component in the assessment of the market value of single real estate objects, based on multiplicative models of market value.Results. The paper clearly shows the reason why the multiplicative model (linear model in the logarithms of prices and some factors) gives better results than the multiplicative one. A method for creating cadastral value tables with changing values of price-forming factors is shown.Conclusion. The paper shows that the share of the land component in the assessment of the cadastral value is not a constant, it largely depends on the values of price-forming factors, primarily such as the area of the land plot, the area of the buildings and structures located on it, the location of the object. The three factors mentioned above can form a certain basic cadastral value (defined as market value), which can be adjusted taking into account the individual characteristics of the object